2003
DOI: 10.1159/000072822
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sevelamer and Calcium Acetate on Proxies of Atherosclerotic and Arteriosclerotic Vascular Disease in Hemodialysis Patients

Abstract: Background: We recently determined that in hemodialysis patients, the use of calcium salts to correct hyperphosphatemia led to progressive coronary artery and aortic calcification as determined by sequential electron beam tomography (EBT) while the use of the non-calcium-containing binder sevelamer did not. Whether the specific calcium preparation (acetate vs. carbonate) might influence the likelihood of progressive calcification was debated. Methods: To determine whether treatment with calcium acetate was spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
67
0
4

Year Published

2004
2004
2018
2018

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(71 citation statements)
references
References 15 publications
0
67
0
4
Order By: Relevance
“…Indeed, when sevelamer was compared to commonly used Ca-based P binders in a large hemodialysis patient group it was found that patients receiving sevelamer had unchanged median coronary artery and aorta calcification scores after 1 yr as opposed to Ca-treated patients whose arterial calcification scores increased 28% over baseline (12). Significantly, although both treatments controlled P levels equivalently, treatment with Ca containing binders led to an increased frequency of hypercalcemic episodes and greater suppression of serum parathyroid hormone (PTH) levels in hemodialysis patients (54,55). Similar effects of sevelamer were also noted in a rat uremia model, where renal calcification was greatly reduced compared to Ca carbonate treatment (56).…”
Section: Can Vascular Calcification Be Controlled?mentioning
confidence: 99%
“…Indeed, when sevelamer was compared to commonly used Ca-based P binders in a large hemodialysis patient group it was found that patients receiving sevelamer had unchanged median coronary artery and aorta calcification scores after 1 yr as opposed to Ca-treated patients whose arterial calcification scores increased 28% over baseline (12). Significantly, although both treatments controlled P levels equivalently, treatment with Ca containing binders led to an increased frequency of hypercalcemic episodes and greater suppression of serum parathyroid hormone (PTH) levels in hemodialysis patients (54,55). Similar effects of sevelamer were also noted in a rat uremia model, where renal calcification was greatly reduced compared to Ca carbonate treatment (56).…”
Section: Can Vascular Calcification Be Controlled?mentioning
confidence: 99%
“…La probabilità di essere trattati con una statina è stata ricavata dallo studio di Chertow e collaboratori: nella coorte sevelamer tale probabilità è del 22%, mentre nella coorte del calcio è del 46% [35]. Tale differenza è in relazione all'efficacia di sevelamer nel ridurre i livelli di LDL-colesterolo.…”
Section: Parametri DI Probabilitàunclassified
“…A differenza del calcio, però, l'uso di sevelamer comporta minori livelli di calcemia, la riduzione dei livelli di PCR, il rallentamento della progressione delle calcificazioni vascolari, una minore incidenza di infarto del miocardio, di angina pectoris e di altre vasculopatie periferiche [34][35][36].…”
unclassified
See 1 more Smart Citation
“…This step has not been proved. Notably, studies of sevelamer hydrochloride showed less progression of calcification compared with calcium-based binders, but no randomized clinical trial showed a survival benefit to sevelamer in intention-to-treat analyses 22 ; therefore, although CAC associates with coronary events and is considered a measure of subclinical atherosclerosis, it is unclear whether regression or less progression of CAC links with improved outcomes. It may be that CAC is yet another critical cardiovascular risk factor, which, like diabetes and hypertension, is now related to low calcidiol levels.…”
mentioning
confidence: 99%